Investigation of Changes in Natural Gas Parameters along a Damaged Gas Pipeline - Victor Dzhyhyrei; Fedir Matiko (Energy Engineering and Control Systems, 2024)
The paper presents a mathematical model of the stationary flow of natural gas in an inclined gas pipeline, which makes it possible to calculate the gas parameters (pressure, temperature, compressibility factor) in every cross-section of gas pipeline. An improved mathematical model is also proposed by the authors, which considers the change in the gas flowrate along the gas pipeline. Complex 1 characterizing the effect of frictional forces and pressure losses and Complex 2 determining the effect of flow velocity were proposed to confirm the need to use an improved mathematical model. Based on the ratio of these complexes, a quantitative criterion was formed for the application of the improved mathematical model. An example of a comparison of complexes for a long pipeline and a short pipeline with a large gas flowrate is presented. Provided that the complexes are of the same order, the relative deviation of the pressures at the end of the gas pipeline obtained by the known and improved model can differ by 8 – 10%. Therefore, in such a case, it is necessary to apply the mathematical model improved by the authors. An example of the application of mathematical models is presented for the analysis of gas pressure and temperature distribution along a gas pipeline with significant damage. The pressure profile along this gas pipeline was obtained for its operating mode with gas flowrate limitation at the inlet and without limitation. It is shown that when the area of ​​damage increases, the change in the pressure profile for these operating modes has features that can be used during the development of a system for determining the volume of gas lost because of sudden damage to gas pipelines.